Design and analysis of a cable driven bio-mimic arm - Wan, Zhi Minh (2009)
The new millennium has seen an exponential increase in the number of robots used across various applications. Apart from the programming required to control any robotic system, the configuration of the manipulator and the selection of joints are also important to achieve a good design. The majority of robots currently in use are serial-configuration with rigid links as it allows easier kinematic control. However, research has shown that robots with parallelconfiguration are viable and have advantages over the serial robots such as higher stiffness and higher loading capacity. In addition, cables provide a good alternative to replace the rigid link systems in driving the robots. Cable-driven parallel robots are light weight and have simple mechanical structure and lower moment of inertia. They are able to achieve larger workspace at higher speeds with lower energy consumption.